IMPLEMENTASI METODE JET TEMPUR DALAM MEMAHAMI ILMU TAJWID DI PONDOK PESANTREN DARUL ULUM DUSUN RASAU KECAMATAN PEMAYUNG KABUPATEN BATANG HARI PROVINSI JAMBI - Awaliyah Masruroh; M. Yahuda (STKIP Pesisir Selatan, 2025)
This study aims to describe the experiences of students, teachers, and researchers at the Darul Ulum Batang Islamic Boarding School. Jet Fighter, as part of the Tajweed textbook, is a learning tool for students. However, it faces challenges in the learning process. The method used in this study is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of this study indicate that the main difficulties faced by students include a lack of accuracy in pronouncing letters according to the letter's pronunciation, limited facilities and infrastructure, and low use of Rosm Uthmani. The results of the study are: (1) the implementation of the Jet Fighter method in Tajweed learning, implemented in class 1 Wostho A and B (male and female), the Quran recitation process took place from 3:30 PM to 5:00 PM with the teacher in the mosque foyer. (2) supporting and inhibiting factors after using the Jet Fighter method in improving understanding of Tajweed, including human resources (HR) and facilities and infrastructure to support the Jet Fighter method. (3) The impact of implementing the jet fighter method on learning the science of tajwid, namely the results felt by the students in the delivery of material, practice, and carefulness in learning.